Profibrogenic role of IL-15 through IL-15 receptor alpha-mediated trans-presentation in the carbon tetrachloride-induced liver fibrosis model - Cloutier, Maryse; Variya, Bhavesh; Akbari, Sara Ali; Rexhepi, Fjolla; Ilangumaran, Subburaj; Ramanathan, Sheela (Frontiers in Immunology, 2024)
Background: Inflammatory cytokines play key pathogenic roles in liver fibrosis. IL-15 is a proinflammatory cytokine produced by myeloid cells. IL-15 promotes pathogenesis of several chronic inflammatory diseases. However, increased liver fibrosis has been reported in mice lacking IL-15 receptor alpha chain (IL-15Rα), suggesting an anti-fibrogenic role for IL-15. As myeloid cells are key players in liver fibrosis and IL-15 signaling can occur independently of IL-15Rα, we investigated the requirement of IL-15 and IL-15Rα in liver fibrosis.We induced liver fibrosis in Il15 -/-, Il15ra -/-and wildtype C57BL/6 mice by the administration of carbon tetrachloride (CCl4). Liver fibrosis was evaluated by Sirius red and Mason's trichrome staining and α-smooth muscle acting immunostaining of myofibroblasts. Gene expression of collagens, matrix modifying enzymes, cytokines and chemokines was quantified by RT-qPCR. The phenotype and the numbers of intrahepatic lymphoid and myeloid cell subsets were evaluated by flow cytometry.Results: Both Il15 -/-and Il15ra -/-mice developed markedly reduced liver fibrosis compared to wildtype control mice, as revealed by reduced collagen deposition and myofibroblast content. Il15ra -/-mice showed further reduction in collagen deposition compared to Il15 -/-mice. However, Col1a1 and Col1a3 genes were similarly induced in the fibrotic livers of wildtype, Il15 -/-and Il15ra -/-mice, although notable variations were observed in the expression of matrix remodeling enzymes and chemokines. As expected, Il15 -/-and Il15ra -/-mice showed markedly reduced numbers of NK cells compared to wildtype mice.They also showed markedly less staining of CD45 + immune cells and CD68 + macrophages, and significantly reduced inflammatory cell infiltration into the liver, with fewer pro-inflammatory and antiinflammatory monocyte subsets compared to wildtype mice.Our findings indicate that IL-15 exerts its profibrogenic role in the liver by promoting macrophage activation and that this requires trans-presentation of IL-15 by IL-15Rα.